Pengaruh Disiplin Belajar dan Lingkungan Teman Sebaya Terhadap Hasil Belajar Siswa Kelas X OTP dan X AKL Pada Mata Pelajaran Administrasi Umum - Afrizal M; Armida S (Universitas Negeri Padang, 2021)
This study aims, 1) to analyze the effect of learning disipline on general learning outcoes of grade X OTP and X AKL students of SMK N 2 Padang, 2) to analyze the influence of peer environment on general administrative learning result of class X OTP and X AKL students of SMK N 2 Padan, 3) to analyze the effect of learning disipline and peer environment together against student learning outcoes of grade X OTP and X AKL students of SMK N 2 Padang. This type of research is quantitative descrptive reseach. The population in this study was class X student. The sampels used were 84 people using proportional random sampling. The type of data in this study primary data. The data collection technique used was a questionnaire. The data that hass been collected is analyzed by descriptive analysis, 1) positive and significant learning disipline on the learning outcomes of general administration subject in class X OTP and X AKL in SMK N 2 Padang, 2) positive and significant Peer Environment in learning outcomes of general administration subject in class X OTP and X AKL in SMK N 2 Padang, 3) disipline of learning and the Environment together have a positive and significant effect on student learning outcomes in class X OTP and X AKL in SMK N 2 Padang.Keywords: learning disipline, peer environment, general learning